Representation of Cultural Values in Local 2D Animation: An Exploratory Study on Student Works - Bawono, Marastika Wicaksono Aji; Aju, Charmiyanti Nurkentjana; Khadijah, Khadijah; Sanwasih, Mochamad; Choiriyati, Nur (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
In the evolving landscape of digital media, 2D animation has emerged as a dynamic tool for cultural preservation, particularly among university students who are increasingly engaging in creative practices that reflect their cultural identities. This study explores how cultural values are represented in local 2D animation works produced by Indonesian students. The research is grounded in the context of the rising importance of culturally informed media content as a means of transmitting tradition to younger audiences in the face of globalization. Employing a qualitative exploratory approach through literature study and content analysis, the research draws on primary data in the form of student-produced animations retrieved from digital platforms and portfolios, and secondary data from academic literature. The study focuses on visual and narrative elements such as costumes, symbols, traditional folklore, character design, and storyline themes that are embedded with local values. Findings reveal that while most student works demonstrate high motivation to preserve cultural heritage and communicate moral messages, there exists a significant variance in the depth of cultural representation. Elements like batik patterns, traditional dances, and folklore-based narratives are visually present, but often lack contextual integration or symbolic depth. Despite these limitations, some animations successfully blend tradition with contemporary issues such as environmental awareness and identity politics, reflecting critical engagement. The study underscores the importance of fostering cultural literacy, interdisciplinary collaboration, and curriculum development in art and animation education to enhance cultural authenticity in student works.